2018
DOI: 10.1002/2017jd027078
|View full text |Cite
|
Sign up to set email alerts
|

Change in Intensity and Frequency of Extreme Precipitation and its Possible Teleconnection With Large‐Scale Climate Index Over the China From 1960 to 2015

Abstract: Understanding the change in intensity and frequency of extreme precipitation plays an important role in flood risk mitigation and water resource management in China. In this study, we analyzed the abrupt changes and long‐term trends in extreme precipitation intensity and frequency over China from 1960 to 2015 based on daily precipitation from stations. The possible teleconnection with large‐scale climate index was also been investigated. The major results are as follows: (1) 14.72% and 23.51% of all the statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 50 publications
8
43
0
1
Order By: Relevance
“…Deng et al [48] Large-scale climate indices were found to have more influence on frequency rather than intensity of extreme precipitation over China.…”
Section: F Chinamentioning
confidence: 99%
“…Deng et al [48] Large-scale climate indices were found to have more influence on frequency rather than intensity of extreme precipitation over China.…”
Section: F Chinamentioning
confidence: 99%
“…Studies around the world have revealed the influences of large-scale circulation changes on weather regimes, climate change, and hydrological variations (Hoerling et al, 2016;Mallakpour and Villarini, 2016;Xiao et al, 2017;Deng et al, 2018). China is mainly influenced by the East Asian Monsoon climate.…”
Section: Introductionmentioning
confidence: 99%
“…The non-parametric Mann-Kendall (M-K) test and Sen's slope estimates were used to calculate trends in the selected time series of temperature and precipitation extremes for the YRB. The M-K test is widely used to analyze the monotonically increasing or decreasing trends in climate change research [43,[52][53][54]. It produces two important parameters: the slope magnitude (change per unit time) in a time series and the statistic Z value that indicates the direction of the trend.…”
Section: Trend Analysismentioning
confidence: 99%
“…The ACPs are commonly expressed by numerical indices determining the intensity of the influence of atmospheric circulation during a specific period in a particular geographical region. Studies around the world revealed the influence of the large-scale atmospheric circulation changes on weather regimes, climate change, and hydrological variations [38][39][40][41][42][43]. China climate types are mainly governed by the East Asian Monsoon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation